Designing dynamic research contests - Jean-Michel Benkert; Igor Letina (University of Zurich, Department of Economics, 2019)
This paper studies the optimal design of dynamic research contests. We introduce interim transfers, which are paid in every period while the contest is ongoing, to an otherwise standard setting. We show that a contest where: (i) the principal can stop the contest in any period, (ii) a constant interim transfer is paid to agents in each period while the contest is ongoing, and (iii) a final prize is paid once the principal stops the contest, is optimal for the principal and implements the first-best.
Keywords: O32; D02; L19; 330; innovation; dynamic contests; research contests; inducement prizes